2001
DOI: 10.1074/jbc.m009561200
|View full text |Cite
|
Sign up to set email alerts
|

UNC-87 Is an Actin-bundling Protein

Abstract: The Caenorhabditis elegans unc-87 gene product is essential for the maintenance of the nematode body wall muscle where it is found colocalized with actin in the I band. The molecular domain structure of the protein reveals similarity to the C-terminal repeat region of the smooth muscle actin-binding protein calponin. In this study we investigated the in vitro function of UNC-87 using both the full-length recombinant molecule and several truncated mutants. According to analytical ultracentrifugation UNC-87 occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(75 citation statements)
references
References 35 publications
2
67
0
6
Order By: Relevance
“…Recombinant UNC-87 and turkey smooth muscle tropomyosin have been shown to simultaneously bind to Factin in vitro (Kranewitter et al, 2001), and we confirmed that UNC-87 and CeTM bind to C. elegans actin (Ce-actin) in a similar manner (Fig. 4A).…”
Section: Unc-87supporting
confidence: 79%
See 3 more Smart Citations
“…Recombinant UNC-87 and turkey smooth muscle tropomyosin have been shown to simultaneously bind to Factin in vitro (Kranewitter et al, 2001), and we confirmed that UNC-87 and CeTM bind to C. elegans actin (Ce-actin) in a similar manner (Fig. 4A).…”
Section: Unc-87supporting
confidence: 79%
“…Although UNC-87 bundles actin filaments in vitro (Kranewitter et al, 2001), this bundling activity is not required for the actin-stabilizing effect. Immobilized actin filaments, which are decorated but not bundled by UNC-87, are still protected from severing by ADF/cofilin (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…p57 297-461 without GST tag was used to cross-link pre-assembled actin filaments and a low speed co-sedimentation assay was utilized to test the effect of cross-linking [23]. At low speed (15,000 × g), neither F-actin nor p57 297-461 alone was pelleted upon centrifugation ( Figure 5).…”
Section: -461 Can Cross-link Actin Filamentsmentioning
confidence: 99%